New records of pollinating flies (Diptera: Bombyliidae, Mythicomythiidae, Syrphidae, and Conopidae) from Slovakia - Marek Semelbauer; Alois Čelechovský; Jindřich Roháček; Ján Samay (Check List)
Eleven species of flies from four families are recorded as new for the fauna of Slovakia: the bee flies (Bombyliidae) Apolysis szappanosi Papp, 2005, Bombylisoma unicolor (Loew, 1855), and Lomatia lachesis Egger, 1859; the micro bee fly (Mythicomyiidae) Platypygus bellus Loew, 1869; the hoverflies (Syrphidae) Callicera aurata (Rossi, 1790), C. spinolae Rondani, 1843, Eumerus hungaricus Szilády, 1940, Myolepta potens (Harris, 1780), Paragus tibialis (Fallén, 1817), and Riponnensia splendens (Meigen, 1822); and the thick-headed fly (Conopidae) Zodion nigritarsis (Strobl, 1902)